2004
DOI: 10.1038/modpathol.3800176
|View full text |Cite
|
Sign up to set email alerts
|

Divergent cyclin B1 expression and Rb/p16/cyclin D1 pathway aberrations among pulmonary neuroendocrine tumors

Abstract: A total of 111 pulmonary neuroendocrine tumors comprising 13 typical carcinoids, five atypical carcinoids, 44 large-cell neuroendocrine carcinomas and 49 small-cell carcinomas were immunohistochemically studied for dysregulated cyclin B1 expression and disruption of the Rb/p16/cyclin D1 pathway (Rb pathway), and the results were correlated with tumor proliferation activity and clinical outcome. Overexpression of cyclins B1 and D1, respectively, was detected in no and 15% typical carcinoids, 20 and 20% atypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…The loss of its function has been observed at an early stage in LCNEC, 43 and others demonstrated that p16 loss affected LCNEC preferentially compared with SCC and was associated with a significantly worse survival. 31,39,41 We observed a positive correlation between p16 loss and extensivestage disease, suggesting a more aggressive phenotype in keeping with previous observations. 31 Finally, none of the molecular markers that we studied differed between pulmonary, extrapulmonary and unknown primary tumor sites.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The loss of its function has been observed at an early stage in LCNEC, 43 and others demonstrated that p16 loss affected LCNEC preferentially compared with SCC and was associated with a significantly worse survival. 31,39,41 We observed a positive correlation between p16 loss and extensivestage disease, suggesting a more aggressive phenotype in keeping with previous observations. 31 Finally, none of the molecular markers that we studied differed between pulmonary, extrapulmonary and unknown primary tumor sites.…”
Section: Discussionsupporting
confidence: 79%
“…[30][31][32] Biologic studies have highlighted markers to distinguish poorly differentiated from well-differentiated tumors and even from subgroups of tumors within these 2 categories. 16,18,21,[33][34][35][36][37][38][39][40][41][42][43] The Loss of retinoblastoma (Rb), p16, and p53 function and increased expression of cyclin D1 and Bcl-2 have been described in LCNEC.…”
Section: Discussionmentioning
confidence: 99%
“…55,63 In SCLC, Rb loss is frequent in SCLC and LCNEC but not in TC and it can be found in 60% of AC. In high-grade tumors, there is an inverse relationship between Rb and P16, and in all neuroendocrine tumors, there is a direct relationship between cyclin D1 and Rb, indicating that p16 and cyclin D1 act exclusively on the Rb pathway for cell-cycle regulation.…”
Section: Ink4mentioning
confidence: 99%
“…These data demonstrate that the RB pathway of G1 arrest is consistently compromised in SCLC and LCNEC, but is intact in TC with intermediate aberrations in AC. 55,63 The C-kit protein expression has been found in high-grade pulmonary neuroendocrine tumors. Frequent positive membranous/cytoplasmic expression in high-grade tumors with 77/44% of LCNEC, 70/ 67% of SCLC was found by Pelosi et al 64 but it was found in only 7% of carcinoid tumors.…”
Section: Ink4mentioning
confidence: 99%
“…This expression is accompanied by cyclin D1 overexpression, a cell cycle associated protein and primary target of Wnt signaling, that has also been reported in neuroendocrine tumors. 3,4 Cyclin D1 expression is often associated with tumor progression in various cancers and a marker of mantle cell lymphoma. 5,6 Phenotypically, most or a considerable number of solid pseudopapillary neoplasms express markers that are related to neuroendocrine features.…”
mentioning
confidence: 99%